Brand Anticipation in an Era of Uncertainty: Understanding Consumer Behaviour towards Companies' Future Anticipation Efforts - Andriya Risdwiyanto; Filasti Rahma; Loso Judianto; Arif Saefudin (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2024)
Modern companies invest heavily in understanding future customer needs, but these efforts are sometimes unappreciated, leading to poor results. This research aims to understand future anticipation by linking it to companies' predictions of technological, cultural, and competitive changes and how consumers perceive these changes. Using qualitative methods, data was collected through semi-structured interviews and focus group discussions (FGD) with eight participants each. The findings show that customers highly value visionary company initiatives, forming positive memories that strengthen brand relationships. These memories, particularly in the precordium area of the brain, impact loyalty and shopping behavior, emphasizing the importance of introspection and personal experience. The research also introduces the concept of "massclusivity" and its relationship with elite consumers, like tablet owners. The novelty of this study lies in applying futurology in marketing and utilizing autobiographical memory. Keywords: consumer behaviour; corporate anticipation; era of uncertainty; future; technology products